The Influence of Charitable Attitudes and Religiosity on the Happiness of Middle Adult Muslims in Jabodetabek - Airlangga, Dean Zulmi; Syahid, Achmad (Psikis : Jurnal Psikologi Islami, 2025)
Happiness is a positive emotional condition that is important in life, especially for middle-aged adults who face various life pressures. This study aimed to examine the effect of generous attitudes and religiosity on the happiness of middle-aged Muslims in the Jabodetabek area. This study used a quantitative approach with volunteer sampling techniques on 200 Muslim respondents aged 40–60 years. The measuring instruments used included the Oxford Happiness Questionnaire, Attitudes Toward Charitable Giving, and the IIUM Religiosity Scale. Data analysis was performed using multiple linear regression. There was a significant influence of all independent variables on happiness (R² = 33.2%, p < 0.05). However, specifically, only the dimensions of faith (p = 0.030) and ihsan (p = 0.002) of religiosity had a significant effect on happiness. Generous attitudes, age, gender, and the Islamic dimension did not show a significant effect. These results indicated that the spiritual aspect of religiosity plays a greater role in shaping happiness than generous attitudes, especially in the middle-aged adult phase. Faith and ihsan are the main predictors of happiness of middle-aged Muslim adults in Jabodetabek. Further studies are recommended to explore other variables such as marital status and social welfare.